2010
DOI: 10.14490/jjss.40.145
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Portfolio Optimization Using Generalized Dynamic Conditional Heteroskedastic Factor Models

Abstract: We model large panels of financial time series by means of generalized dynamic factor models with multivariate GARCH idiosyncratic components. Such models combine the features of dynamic factors with those of a generalized smooth transition conditional correlation (GSTCC) model, which belongs to the class of time-varying conditional correlation models. The model is applied to dynamic portfolio allocation with Value at Risk constraints on 6.5 years of daily TOPIX Sector Indexes. Results show that the proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In order to investigate this, the APARCH(1,1), APARCH-X(1,1), and APARCH-CJ(1,1) models are compared by using 1-minute intraday high-frequency data from the Tokyo Stock Price Index (TOPIX) in Japan. A study of [10] showed that APARCH models have better performances compared with the GARCH model for the daily TOPIX Sector Indexes, which suggests the existence of an asymmetric effect. To our knowledge, there are no results for the estimation of the APARCH-CJ model.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate this, the APARCH(1,1), APARCH-X(1,1), and APARCH-CJ(1,1) models are compared by using 1-minute intraday high-frequency data from the Tokyo Stock Price Index (TOPIX) in Japan. A study of [10] showed that APARCH models have better performances compared with the GARCH model for the daily TOPIX Sector Indexes, which suggests the existence of an asymmetric effect. To our knowledge, there are no results for the estimation of the APARCH-CJ model.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, the market and the stock-specific components are assessed independently in an attempt to improve the covariances estimates (SHIOHAMA et al, 2010).…”
Section: A Note On the Homoscedasticity Hypothesis And Future Work Including Markov Chainsmentioning
confidence: 99%